Confirmation of GmPPR576 as a fertility restorer gene of cytoplasmic male sterility in soybean - Wang, Tanliu (Journal of experimental botany, 2021)
© The Author(s) 2021. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.